O cavaquinho na obra de Waldir Azevedo - Cesar, Ana Claudia (2011)
This work intend to describe the way that the musical instrument named cavaquinho took as fundamental piece at the formation of the choro as a musical gender. Besides, this research shows how the composer Waldir Azevedo transformed the old way of the cavaquinho, an instrument used to accompany to an instrument that could be (played) solo. Initially an approach was done about the history of the choro and a bibliographic research about Waldir Azevedo. Four pieces of this author were selected for this work and also an attentive musical analysis of his interpretations playing the cavaquinho was done. Through this, it was possible to realize the specific methodology used by him to play and to build his works